Kontribusi Zakat terhadap Pengurangan Kesenjangan Sosial Ekonomi Masyarakat Muslim - Epih Hapiyatul Apiah; Nurul Millah; Muhammad Rofiun Rutab; Sarif Hidayat; Abu Lubaba (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
Zakat is one of the instruments of Islamic economics that serves both social and economic functions in promoting equitable social welfare. The persistently high level of socio-economic inequality in many Muslim countries has positioned zakat as an alternative solution for wealth redistribution and poverty alleviation. This study aims to analyze the contribution of zakat to reducing socio-economic inequality among Muslim communities based on various published studies. The research method employed is a literature review by examining relevant scientific articles from national and international journals published between 2020 and 2025. The findings indicate that zakat significantly contributes to reducing socio-economic inequality through income redistribution mechanisms, economic empowerment of mustahik (zakat beneficiaries), poverty reduction, and improvements in community welfare. Furthermore, productive zakat programs have been proven to be more effective in fostering economic independence compared to consumptive zakat. However, the effectiveness of zakat still faces several challenges, including low public awareness, suboptimal fund collection, and less-than-optimal governance of zakat institutions. Therefore, strengthening a professional, transparent, and technology-based zakat management system is necessary to enhance its contribution to achieving socio-economic justice within Muslim communities.